Design of security system based on immune system - Nishiyama, H.; Mizoguchi, F. (Proceedings Tenth IEEE International Workshop on Enabling Technologies: Infrastructure for Collaborative Enterprises. WET ICE 2001, 2001)
The authors design a network security system using an analogy of natural world immunology. We apply not only the immune mechanism that recognizes self or non-self, but also cooperation among immune cells of the system. This system defines an immune cell as one agent based on our multiagent language, which is an extension of concurrent logic programming languages. These agents can detect and reject intrusion by cooperating with each other.